ANALISIS PEMBELAJARAN JARAK JAUH BERBASIS INTERNET PADA MASA PANDEMI COVID-19 DI SD NEGERI WIDORO YOGYAKARTA - Tarigan, Ema Nina Br; Arief, Ardian (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2021)
The purpose of this study was to determine the process, supporting factors, inhibiting factors, and efforts to overcome obstacles to the implementation of distance learning. The data in this article were collected and processed using qualitative methods. The data collection techniques used observation, interview, and documentation techniques. Data analysis techniques used the analysis of the Miles and Huberman model which consists of data collection, data reduction, data display, and verification. The results show that (1) the internet-based distance learning process is carried out using the WhatsApp application, google meets, and Google Forms. (2) Supporting factors for implementing distance learning namely students are encouraged to be more independent in learning, teachers, school principals, and parents to collaborate, and use internet networks. (3) The inhibiting factor is that there are still some students who still do not understand the material, do not have complete facilities and lack guidance from parents. (4) Efforts to overcome obstacles The principal is holding meetings with the teacher twice a week, the teacher making creative learning videos, working with parents in supervision, and the teacher explaining again when meeting in person at school.